2022
DOI: 10.3389/fimmu.2022.978262
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd3/IRF4 axis aggravates myeloid fibroblast activation and m2 macrophage to myofibroblast transition in renal fibrosis

Abstract: Renal fibrosis commonly occurs in the process of chronic kidney diseases. Here, we explored the role of Jumonji domain containing 3 (Jmjd3)/interferon regulatory factor 4 (IRF4) axis in activation of myeloid fibroblasts and transition of M2 macrophages into myofibroblasts transition (M2MMT) in kidney fibrosis. In mice, Jmjd3 and IRF4 were highly induced in interstitial cells of kidneys with folic acid or obstructive injury. Jmjd3 deletion in myeloid cells or Jmjd3 inhibitor reduced the levels of IRF4 in injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Bae et al demonstrated that glycolysis negatively regulates proinflammatory responses in inflammatory macrophages by mediating IRF4 17 . Liang et al indicated that Jmjd3/IRF4 axis is involved in myofibroblast transition in renal fibrosis via aggravating myeloid fibroblast activation as well as M2 macrophage 34 . Additionally, Shohan et al indicated that IRF4 expression was elevated in the inflamed mucosa of UC patients, mirroring that IRF4 has a crucial role in UC development 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bae et al demonstrated that glycolysis negatively regulates proinflammatory responses in inflammatory macrophages by mediating IRF4 17 . Liang et al indicated that Jmjd3/IRF4 axis is involved in myofibroblast transition in renal fibrosis via aggravating myeloid fibroblast activation as well as M2 macrophage 34 . Additionally, Shohan et al indicated that IRF4 expression was elevated in the inflamed mucosa of UC patients, mirroring that IRF4 has a crucial role in UC development 35 .…”
Section: Discussionmentioning
confidence: 99%
“…(A) and (B) flow cytometry analysis was used to detect the percentage of CD11b + CD86 + cells and CD11b + CD86 + cells affected by Bcl6 and recovered by IRF4 in dextran sulfate sodium (DSS) induced UC mice; (C) enzyme-linked immunosorbent assay was used to detect the secretion of TNF-α, IL-1β, IL-6, and IL-10 affected by Bcl6 and recovered by IRF4 in DSS induced ulcerative colitis (UC) mice. *, p < .05; ****, p < .0001.Jmjd3/IRF4 axis is involved in myofibroblast transition in renal fibrosis via aggravating myeloid fibroblast activation as well as M2 macrophage 34. Additionally, Shohan et al indicated that IRF4 expression was elevated in the inflamed mucosa of UC patients, mirroring that IRF4 has a crucial role in UC development 35.…”
mentioning
confidence: 99%
“…This population of cells may arise from a further differentiation of M2, as evidenced by the expression of M2 markers including CD206 ( 22 ). Over the past few years, several studies conducted by different research groups have reported the presence of MMT and its critical role in kidney fibrosis ( 14 , 22 , 23 , 79 , 80 ). However, recent single-cell sequencing data does not provide substantial evidence supporting a significant contribution of myofibroblasts originating from macrophages ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…JAK3/STAT6 signaling, Jumonji domain containing 3 (Jmjd3)/interferon regulatory factor 4 (IRF4) axis, and natural killer T cell/IL-4 signaling can activate myeloid fibroblasts, promoting the transition of M2 macrophages into myofibroblasts in kidney fibrosis in obstructed mouse kidneys [216][217][218]. Myeloid Jmjd3 deletion or Jmjd3 inhibitor reduced the expression of IRF4, α-smooth muscle actin, and fibronectin, inhibiting MMT in cultured monocytes exposed to IL-4.…”
Section: Strategies To Inhibit the Transition Of Macrophages Into Myo...mentioning
confidence: 99%